Experimental Evaluation of a Shoulder-Support Exoskeleton for Overhead Work: Influences of Peak Torque Amplitude, Task, and Tool Mass. Issue 3 (2nd October 2019) - Van Engelhoven, Logan; Poon, Nathan; Kazerooni, Homayoon; Rempel, David; Barr, Alan; Harris-Adamson, Carisa
OCCUPATIONAL APPLICATIONS: In this study, we explored the effects of peak torque amplitude (PTA) provided from a passive shoulder-support exoskeleton (shoulderX) on muscle activation, preference, and perceived exertion. Use of the exoskeleton during both sustained and repetitive overhead tasks reduced bilateral shoulder flexor muscle activity with increasing levels of PTA. Muscle activation was reduced by up to 81%, and participants reported reduced perceived exertion when wearing the device compared to an unassisted condition. Use of the exoskeleton was preferred by all participants, versus an unassisted condition, though the preferred level of PTA varied across participants. In occupational use, a properly chosen support level may help reduce the risk of injury associated with performing overhead tasks. TECHNICAL ABSTRACT: Background : Shoulder-support exoskeletons assist workers performing overhead tasks by providing assistive torque to the upper extremities. Although the application of shoulder-supporting exoskeletons to overhead tasks appears promising for reducing physical demands, the optimization of exoskeleton torque for workers of varying sizes performing tasks with different demands is lacking. Purpose : The purpose of this study was to evaluate the physical and subjective impacts of different peak torque amplitudes (PTA), during overhead work with differing tasks demands. Methods : We evaluated the shoulderX exoskeleton in a laboratory setting among 14 male participants, by measuring bilateral median and peak muscle activation, preference, and perceived exertion (subjective responses were only available for half of the sample). Four PTA support levels (5, 10, 15 Nm peak torque) were applied, along with a comparison condition without the exoskeleton (i.e., unassisted), while participants performed both a sustained and a repetitive overhead task using light (0.45 kg) and heavier (2.25 kg) tools. Results : Compared to the unassisted condition, anterior deltoid and upper trapezius activity decreased with increasing PTA, where median activities were reduced by up to 81% and 46%, respectively. Shoulder extensor (antagonist) muscle activity results were inconsistent across subjects. Perceived exertion was reduced across the shoulder and back compared to the unassisted condition. All participants preferred the use of the shoulderX over the unassisted condition, but the preferred PTA setting varied between participants. Conclusions : The shoulderX significantly reduced overall median and peak muscle activity during static and repetitive overhead tasks using light and heavier tools, and thus may be an important approach to help reduce the risk of work-related shoulder fatigue and injury. The magnitude of PTA preferred by participants varied, and excessive PTA increased antagonist muscle activity for some participants. Therefore, selecting the PTA level is likely an important factor in maximizing reductions in shoulder flexor muscle activity while avoiding negative impacts to preference or antagonist muscle activity.